Effect of Patching on Reducing Restenosis in the Carotid Revascularization Endarterectomy Versus Stenting Trial. Issue 3 (March 2015) - Malas, Mahmoud; Glebova, Natalia O.; Hughes, Susan E.; Voeks, Jenifer H.; Qazi, Umair; Moore, Wesley S.; Lal, Brajesh K.; Howard, George; Llinas, Rafael; Brott, Thomas G.
Abstract : Background and Purpose—: The purpose is to determine whether patching during carotid endarterectomy (CEA) affects the perioperative and long-term risks of restenosis, stroke, death, and myocardial infarction as compared with primary closure. Methods—: We identified all patients who were randomized and underwent CEA in Carotid Revascularization Endarterectomy versus Stenting Trial. CEA patients who received a patch were compared with patients who underwent CEA with primary closure without a patch. We compared periprocedural and 4-year event rates, 2-year restenosis rates, and rates of reoperation between the 2 groups. We further analyzed results by surgeon specialty. Results—: There were 1151 patients who underwent CEA (753 [65%] with patch and 329 [29%] with primary closure). We excluded 44 patients who underwent eversion CEA and 25 patients missing CEA data (5%). Patch use differed by surgeon specialty: 89% of vascular surgeons, 6% of neurosurgeons, and 76% of thoracic surgeons patched. Comparing patients who received a patch versus those who did not, there was a significant reduction in the 2-year risk of restenosis, and this persisted after adjustment by surgeon specialty (hazard ratio, 0.35; 95% confidence interval, 0.16–0.74; P =0.006). There were no significant differences in the rates of periprocedural stroke and death (hazard ratio, 1.58; 95% confidence interval, 0.33–7.58; P =0.57), in immediate reoperation (hazard ratio, 0.6; 95% confidence interval, 0.16–2.27; P =0.45), or in the 4-year risk of ipsilateral stroke (hazard ratio, 1.23; 95% confidence interval, 0.42–3.63; P =0.71). Conclusions—: Patch closure in CEA is associated with reduction in restenosis although it is not associated with improved clinical outcomes. Thus, more widespread use of patching should be considered to improve long-term durability. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00004732.